Trust influence towards internet banking acceptance among postgraduate students at UTM Kuala Lumpur campus - Fadhilah, Bilqish (2014)
Recent development in online technologies and devices, as well as the diversity of internet usage in daily life, has made internet banking as a necessity in our daily life. Online transaction has become a common practice in our society, especially in Malaysia. It is essential for financial institution, especially banks, to recognize determinants that influence user intention in using internet banking in order to provide suitable internet banking system. The objective of this study is to understand the determinants that influence user intention in using internet banking and proposed a conceptual model that illustrate the relationship among the determinants. Technology Acceptance Model theory was used as theoretical foundation to examine the determinants which comprise perceive ease of use, perceive usefulness, trust, and determinants of trust including familiarity with bank, structural assurance, situational normality, and calculative-based trust. This study was applying quantitative methodology by collecting 274 data from postgraduate students at UTM Kuala Lumpur. Furthermore, data analysis techniques of Correlation and Multiple Linear Regression Analysis were utilized to test the hypotheses of this study. The result of this study reflected that familiarity with bank, structural assurance, calculative-based trust and perceive ease of use have influence towards trust, which furthermore affect user perceive usefulness and intention in using internet banking. Finally, providing the determinants of internet banking usage helps financial institution to develop and implement more efficient system.